LEXICAL SEMANTIC ANALYSIS OF THE MUSICAL INSTRUMENTS ANGKLUNG SERED, ANGKLUNG LANDUNG, AND KARINDING - Ahmad Taufik; Angelina Sepiani Kusmawati; Mutiara Dwi Utami; Aveny Septi Astriani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research aims to explain and classify words that have lexical meaning on the musical instruments angklung sered, angklung landung, and karinding. The approach used in this research is lexical semantic theory. Lexical semantics is the study of meaning related to words according to the dictionary. This research uses a qualitative descriptive method and is included in one approach to analyzing a literary work. The method used in this research is a qualitative descriptive method. Qualitative descriptive is a technique of describing and interpreting the meaning of the data that has been collected by paying attention to and recording aspects of the situation being studied at that time so as to get a general and comprehensive picture of the actual situation (Kriyantono, 2007). The data collection technique used in this research is the literature study technique. This technique is used to examine books, literature, notes and reports that are related to the problem to be solved.